(untitled) (مجلة إحالات, 2026)
This article—as the titlesuggests—addresses a topic related to the educationalfieldfrom the perspective of a genius man whowasahead of his time in thought, knowledge, and wisdom: Abdelhamid Ben Badis. He left an enduringlegacy for Algeria and the Arab and Islamic world acrossvariousspheres of religious, political, social, historical, and educational life. Hisprimaryconcernwas the renaissance of the Algerian people as a whole, and the youth in particular, lifting themfrom the depths of ignorance, illiteracy, and tyranny. He presented us with numerous reform projects, foremostamongthemhiseducationalproject. In thisendeavor, hedevotedhisutmost efforts, balancing the aim of reform—to dismantle colonial-erarubble and combat the colonial strategy of keeping the people ignorant—with the aim of renewal—to build a comprehensiveeducationalapproach capable of cultivatinghighlymotivatedcompetencies, rooted in authenticbelonging, and sound in thinking and knowledge.